Urethrotomy and End-to-End Urethroplasty in Anterior Urethral Strictures upto 1.5cm Dept of Urology Mayo Hospital, Lahore - Imran Ansari, Shams Ul Islam, Wajid Ali, Irfan Ul Haq, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare internal optical urethrotomy with end-to-end urethroplasty in treatment of anterior urethral stricture (<1.5cm) in terms of recurrence. Study design: Cross-sectional Study. Place and duration of study: Mayo hospital, department of urology. June 2016 to July 2018 Methodology: Only 80 patients (40 individuals in each class) were included in the study with nonprobability convenience sampling. Urethral stricture of the same length was treated by class-A and class-B, but with different methods. 3 months after the initial diagnosis, the recurrence rate was examined. SPSS-22 was used to enter and analyse the data. Result: Patients' recurrences three months later indicated a significant difference (P=0.002) as a P value less than 0.05. A recurrence rate of 20% was found in class A end-to-end urethroplasty patients, whereas a stricture-free rate of 80% was found in the other 32. Stricture recurrence was seen in 52.5% of the patients in class B (internal optical urotomy), compared to 47.5% in class A. Conclusion: A urethroplasty is the best therapy for urethral strictures of 1.5 cm or more, according to this research. For the most part, the fundamental distinction between the two procedures is that urethroplasty has a lower rate of repeat surgeries than that of the other procedure. Keywords: Stricture urethra, Urethroplasty, Recurrence, Dilation, Urine obstruction,